Instrumenty komunikowania marketingowego w dobie globalizacji - Kozłowska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
A global market necessitates including the evolution of consumer awareness and the growing importance of consumers in marketing activities. This process including utilizing existing instruments of marketing communication along with a new look at consumer motivations (and at information about products). Among the major changes in consumer attitudes and behavior worldwide are the following phenomena: more negative attitudes toward advertising, increasing consumer attention to ethical aspects of business, greater environmental awareness, and growing consumer product expectations. Th e study shows a close relationship between social and technological changes. New information technology provides new opportunities for contact with consumers and between consumers. It is expected that the current traditional model of communication with the market, based on information derived from opinion leaders (from athletes, experts, celebrities), in the interactive communication model will be lead to horizontal influence derived from individual consumers. Consumers become not only active seekers of market information, but also creators and relayers of this information rather than defenseless recipients. Furthermore the responsible consumer is a person who not only knows his or her rights, but also supports a particular producer through purchases. Access to information about companies (and their products) through new media (mobile, internet) allows the consumer to control activities of commercial organizations (particularly multinational corporations) without geographic limitations. Not so long ago, the most important goal was to provide products conveniently to consumers at an attractive price. Now it seems that brand imaging is increasingly created by consumers themselves, who in turn create brand history among themselves. New patterns of consumer behavior give rise to new marketing (and communication) strategies. Of course, many consumers do passively participate in the process of marketing communication. However, we must assume that this new generation of responsible consumers determines a clear direction of changes in business -consumer relationships.